Ferrous base materials performance in seawater and its failure analysis - Seoh, S.Y.; Mohammed Misbahul, Amin; W. B., Wan Nik; N. Kancono; M. S. Azhar; H. B. Senin (Kolej Universiti Sains dan Teknologi Malaysia, 2009)
The effect of seawater to the corrosion behavior of ferrous base steel AISI 1053 have been determined at room temperature. The corrosion products were characterized by using energy-dispersed X-ray spectroscopy (EDS), and Scanning Electron Microscope (SEM). The alloys show thick, loose and porous films deposits on the surface of alloys. The deposit scales showed complex microstructures and compositions, exhibiting deleterious effect on the surface of alloy.